A representação do movimento para salvar o Jóquei Clube de Goiás pela imprensa goiana - Azevedo, Natane Rincon (2023)
This master's thesis analyzes how the representation of the movement and the process of listing of the Jóquei Clube de Goiás by the main newspapers from Goiânia would relate to the history of struggles for the listing of cultural assets in Brazil and in Goiânia. In 2017, the sale of the Jóquei Clube de Goiás was negotiated with the Universal Church. If the sale went through, the club's headquarters could be demolished. Thus, a movement, named #salvejóquei on social media, emerged to "save" the club. Simultaneously, the Council of Architecture and Urbanism of Goiás (CAU-GO) filed a process for the listing of Jóquei's headquarters as a cultural heritage of Brazil. These events received wide coverage from the main newspapers in Goiânia, such as O Popular, Diário da Manhã and Jornal Opção. To analyze this representation, we resorted to the analyzes of collective memory, by Halbwachs (1990), Albuquerque Junior (2007) and Ricoeur (2007); the field of cultural heritage disputes and the history of listing in Brazil, by Chuva (2009), Rodrigues (2001) and Campos (2019); the rhetoric of loss and national identity, according to Gonçalves (1996); among others; united with theories from media studies, by Traquina (2012, 2016), Tuchman (1999), Wolf (2012), etc. For this purpose, we used the method Discourse Analysis to analyze the representation of the three newspapers.